PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER DALAM PROSES PELATIHAN TARI NGEREMO DI PUSDIKLAT TARI ANJUNGAN JAWA TIMUR TAMAN MINI INDONESIA INDAH - Ndaru Dwi Rahayu; Romi Nusyam; Deden Haerudin (Program Studi Pendidikan Tari FBS UNJ, 2024)
This study aims to examine the Ngeremo dance training process at the Dance Training Center (Pusdiklat) of the East Java Pavilion at Taman Mini Indonesia Indah, including the methods of instilling character values in students and the role of Pusdiklat in this training. Using a descriptive qualitative approach, data were collected through observation, interviews, documentation, and literature studies, with triangulation techniques used to validate the data. The results show that Ngremo dance is a required subject at Pusdiklat, divided into levels: Ngeremo Muda for Indria class, Ngeremo Madya for A1 class, Ngeremo Sanggit for A2 class, and Ngeremo Jombangan or Bolet for B class. Character values such as religiosity, honesty, discipline, a sense of family, and self-confidence are instilled through lectures and practical exercises. The findings reveal that Pusdiklat plays a significant role in character development through structured and tiered approaches within the Ngeremo dance training. The character values fostered among students include (a) religiosity, (b) honesty, (c) discipline, (d) a sense of family, and (e) self-confidence. This study provides data on the Ngremo dance training process, methods of instilling character values, and the role of Pusdiklat at Taman Mini Indonesia Indah.